The hidden costs of control: an unsuccessful replication study - Matteo Ploner; Anthony Ziegelmeyer (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This note reports a replication study of Falk and Kosfelds (2006) medium control treatment. In the experimental game, an agent has an endowment of 120 experimental currency units and decides how much to transfer to a principal. For every unit that the agent gives up, the principal receives two units. Before the agent decides how much to transfer voluntarily, the principal decides whether or not to control the agent by imposing a compulsory transfer of 10 units. Like the original study, we observe that control entails hidden costs. Unlike the original study, we do not observe that the hidden costs of control outweigh the benefits and we observe that most of the principals decide to control the agent.
Keywords: C91; M52; 330; Control; Experimental Economics; Incentives; Intrinsic Motivation; Trust; Kontrolltheorie; Leistungskontrolle; Motivation; Agency Theory; Test